La tête qui fume de l’église de Nārgā - Claire Bosc-Tiessé (Afriques)
In the church of Nārgā Śellāsē, built in the years 1738-50, a very unusual sculpture depicts a man smoking. This representation is surprising for we generally think that smoking was highly condemned in the Christian society. It is however what texts from the end of the nineteenth century assert. However pictures and archaeology give contradictory information on that practice. It leads us to reconsider the history of written sources. From the sixteenth to the twentieth century, smoking was stigmatized as a pagan tradition in order to designate the “alien” and, thus, to assert the domination of the Christian State on the region of the Southern Choa. To come back to the carving of Nārgā, the position of the sculpture inside the church according to the liturgy confirms that the association of this image with the “arrogant king” was used to create a religious representation of evil.